Milk Bank Pooling Practices Impact Concentrations and Variability of Bioactive Components of Donor Human Milk - Young, Bridget E.; Murphy, Katherine; Borman, Laraine L.; Heinrich, Rebecca; Krebs, Nancy F. (Frontiers in Nutrition, 2020)
Background: Donor human milk (DHM) bank practices, such as pasteurization and pooling according to postpartum age of milk donations and number of donors included in a pool may impact the resulting concentration of bioactive components of DHM. Aims: We determined the impact of Holder pasteurization, postpartum milk age, and pool donor number (number of donors included in a pool) on resulting concentrations of total immunoglobulin A (IgA; which provides immune protection to the recipient infant) and insulin (an important hormone for gut maturation). We also documented inter-relationships between these bioactive components and macronutrients in DHM pools. Methods: Pre and post-pasteurization aliquots of 128 DHM samples were obtained from the Rocky Mountain Children’s Foundation Mother’s Milk Bank (a member of the Human Milk Banking Association of North America, HMBANA). Macronutrients were measured via mid-infrared spectroscopy. Total IgA was measured via customized immunoassay in skim milk and insulin was measured via chemiluminescent immunoassay. Results: Mean post-pasteurization total IgA concentration was 0.23 ± 0.10 (range: 0.04 – 0.65) mg/mL (n=126), a 17.9% decrease due to pasteurization (n=126). Mean post-pasteurization DHM insulin concentration was 7.0 ± 4.6 (range: 3-40) µU/mL, a decrease of 13.6% due to pasteurization (n=128). The average DHM pool postpartum milk age was not associated with total IgA or insulin concentrations, but pool donor number was associated with bioactive components. Pools with only one donor had lower total IgA and lower insulin concentrations than pools with at least 2 donors (p<0.05). Increasing the number of donors in a pool decreased the variability in total IgA and insulin concentrations (p<0.04). Conclusion: Increasing the number of donors included in DHM pools may help optimize bioactive components in DHM received by premature infants. These results help inform milk banking practices to decrease compositional variability in produced DHM pools.